Water consumption of cotton in the semi arid tracts of India - SENGUPTA, S.; DAS , H. P.; KALE, A. A. (MAUSAM, 2002)
In the present study, evapotranspiration and other agrometeorological data for three different locations, viz., Akola. Bellary and Kovilpatti have been utilized to understand consumptive use and related aspects of cotton. Ratios of evapotranspiration to potential evapotranspiration (ET/PET) and evapotranspiration to total shortwave radiation (ET/Rs) increase gradually as the vegetative cover develops and shows year to year variation at same location. The energy summation indices have been worked out for all the three stations which indicate that the total yields are more dependent on consumptive water use by crop rather than energy summation indices.. The water use efficiency (WUE) of cotton crop also reveals wide variations in time and space.